ACADEMIC STAFF’S SOCIAL-PERSONAL DOMINANT ACTIVITY - Khoruzha, Liudmyla; Melnychenko, Olha (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article deals with the social-personal competences of a modern academic staff, the content of which varies in the conditions of the modern world’s transformations. The peculiarities of such teacher competences are characterized as socio-cultural, professional and personal responsibility, leadership, and civil. The results of such formations for the academic staff of 4 countries (Ukraine, Poland, Czech Republic, Slovakia) who are participants of the international project “High school teacher competence in change" No. 21720008 were presented. The project was carried out in 2018 with the financial support of the Visegrad Fund and the Ministry of Foreign Affairs of the Netherlands. The problem of developing socio-personal competences of academic staff’s is connected with their ability to solve complex issues in various spheres independently and other spheres of activity on the basis of the creative usage of their own, social experience, solving cognitive, philosophical, moral, and communicative tasks. The article gives recommendations for improving the socio-personal dominant activity of academic staff.